The effectiveness of Habitat for Humanity as a neighborhood stabilization program: The case of Charlotte, North Carolina. Issue 4 (8th August 2017) - Delmelle, Elizabeth C.; Morrell, Elizabeth; Bengle, Tara; Howarth, Joe; Sorensen, Janni
Abstract: Habitat for Humanity has been in operation since 1976 as a popular organization that provides housing to low-income families. In more recent years, the organization has gradually shifted its priorities toward becoming a more holistic neighborhood stabilization program, receiving a large amount of federal funding to help stabilize neighborhoods in the wake of the Great Recession. Very limited research has been done to assess the effectiveness of Habitat construction on neighborhood outcomes. This article provides a quantitative assessment of housing price values in Charlotte, North Carolina in neighborhoods that underwent a greater than average amount of Habitat construction compared to a set of similar neighborhoods with no Habitat activity. Using an adjusted interrupted time series model, we find little evidence that Habitat had a substantive impact on housing values compared to control neighborhoods.